Library-faculty collaboration in the development of an accredited phd course in transferable academic skills: A mixed-methods study - Sundstøl, Shea Allison; Nordsteien, Anita (Septentrio Conference Series, 2020)
Background: The PhD course Literature Management and Scientific Communication was establishedin 2019 through a library-faculty collaboration. This is the first accredited generic PhD course at this university, and it provides 5 ECTS credits. In the first course, there werep articipants from four of our eight PhD programs, researching topics spanning from religion to robotics. Our main idea was that bringing PhD candidates from different programs together for such a course may add extra value in the form of enhancing communication and understanding across the disciplines. Methods: The study has a mixed methods design. A preliminary survey was conducted in 2017 to revealthe PhD candidates’ information needs, which provided a basis for planning the course content. To examine the candidates’ learning outcomes and further improvements for future courses, NVivo was used to analyse observations that were recorded during the course, in addition to the participants’ course essays and evaluation forms. Results: The 2017 survey had a response rate of 43% (n = 91). More than 50% of the respondents expressed a need for library courses in literature searching, systematic reviews, research data management and the publishing process. The PhD course was designed based on these findings, and we overbooked the course having accepted 20 participants, including 5 international candidates. The main finding was that several of the participants found the course surprisingly useful to their research and to their career plans. However, there were widely varying opinions about including such a diverse group. Discussion: Having a generic course for early-stage researchers from such a diversity of fields was challenging, and the article discusses several issues to consider for future courses. Most importantly, the prior knowledge was vastly different among the participants. This emphasizes the need for increased library-faculty collaboration to reach out to all PhD candidates in an early stage.